Analisis Performansi dan Ekonomi PLTS Atap 10 kWp pada Bangunan Rumah Tangga di Desa Batuan Gianyar - Riawan, Govinda; Kumara, I Nyoman Satya; Ariastina, W. G. (Majalah Ilmiah Teknologi Elektro; Vol 21 No 1 (2022): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2022)
The Efforts to accelerate the development of renewable energy power plants continue to be driven by the central government as stipulated in the National Energy General Plan. One of the plants developed is the Solar Power Plant. Currently about Solar Power Plant in Indonesia is built to reach 152.44 MW from the target set at 6.5 GW. The central government through the Minister of Energy of Resources and Minerals issued policy No. 49 of 2018 on the use of rooftop power plants. Gianyar is one of the areas that have good solar irradiation with an average of 4.99 kWh/m2/day, where it is very potential to build a rooftop PV. This research aims to find out the study of electrical energy and ecomonic generated from Solar Power Plant 10 kWp in Batuan village. Furthermore, surveyed the field to collect data to simulate the performance, comparison, and investment feasibility of the construction of the Solar Power Plant. Data collection of real production and real consumption is carried out for 12 months. Simulations use PVsyst programs and investment feasibility using several methods, such as Net Present Value.(NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Profitability Index (PI), and Payback Period (PP). The total potential Solar Power Plant in of Batuan Village household is 9.3 kWp from the entire roof of the installation of 78.11 m2. The construction of Solar Power Plant in households in Batuan Village with a capacity of 10 kWp has a potential of 6336.3 kWh in a year with a performance of 30.9%, while in real production this Solar Power Plant is able to produce a total of 8,502 kWh in a year. In economic analysis, the feasibility level of plts development investment was declared unfit, with an NPV value of Rp. - 321,004,050 at a discount rate of 10%, the value of IRR - 90.4%, BCR worth 0.78, PI at 0.32, and PP which reached 78 years.